Implementation Accountancy Environment in Perspective Company Size, Standard Environmental Accounting and Management Environment - Ladewi, Yuhanis; Putri, Afifah Mulya; Mizan; Junaidi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This study aims to find out and analyze the influence of Company Size, Environmental PSAK, and Environmental Management on the Implementation of Environmental Accounting in Mining Companies in Tanjung Enim. The types of research used are descriptive and associative research. The variables used in this study include company size, environmental PSAK, environmental management, and the application of environmental accounting. The sample used was purposive sampling, consisting of 4 companies and 45 respondents. The data used includes primary and secondary data. The data collection technique uses questionnaire techniques, data testing with validity and reliability tests. The data analysis techniques used are descriptive and inferential statistics. The results of the study based on respondents' answers showed that all variables were valid and reliable.  The multiple linear regression test shows that every increase in company size, environmental PSAK, and environmental management by 1 unit will increase the application of environmental accounting. The results of the t-test calculation showed that the environmental financial accounting standard statement (PSAK) did not have a significant effect on the implementation of environmental accounting, while the size of the company and environmental management had an effect on the implementation of environmental accounting.